2004
DOI: 10.1007/s10960-004-5793-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological consequences of the 1999 earthquake in Turkey

Abstract: We explored the prevalence of posttraumatic stress disorder (PTSD) and its relation to demographic characteristics and other risk factors for developing PTSD in a large sample (N = 910) of earthquake survivors living in tent city. Twenty-five percent of the sample met DSM-IV criteria for PTSD assessed with the Posttraumatic Stress Disorder Self Test (PTSD-S). Peritraumatic factors explained the most variance when the risk factors were grouped as demographics, pretraumatic, peritraumatic, and posttraumatic. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 21 publications
5
61
1
Order By: Relevance
“…As mentioned before, there are multiple factors that would place the Haitian student population in the Dominican Republic at a higher risk level, such as being a minority in the country (Brewin et al, 2000), coming from and living in an underdeveloped country (Tural et al, 2004), which could explain why our results are higher than the ones observed by other authors.…”
Section: Resultscontrasting
confidence: 66%
See 3 more Smart Citations
“…As mentioned before, there are multiple factors that would place the Haitian student population in the Dominican Republic at a higher risk level, such as being a minority in the country (Brewin et al, 2000), coming from and living in an underdeveloped country (Tural et al, 2004), which could explain why our results are higher than the ones observed by other authors.…”
Section: Resultscontrasting
confidence: 66%
“…It is possible that various factors affecting this particular group are responsible for the high prevalence of PTSD symptoms found. The effect of being from a developing country (Tural et al, 2004), having minority status in the country were the study was conducted (Brewin, Andrews, & Valentine, 2000), as well as living far from their families (Parvaresh & Bahramnezhad, 2009), cannot be denied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant decrease in respiratory symptoms in Turkish victims in the first post-disaster year may be related with the finding that the Turkish already had a high predisaster level of these symptoms, higher than the Dutch victims. However, respiratory symptoms were not found among the health effects of large-scale earthquakes on Turkish victims Basoglu et al 2004;Kilic and Ulusoy 2003;Livanou et al 2002;Tural et al 2004). Only one disaster study on Turkish victims found "trouble in getting breath" as a somatisation symptom (Karanci and Rustemli 1995), and we may not conclude, therefore, that the decrease in respiratory symptoms was culturally influenced, since so little is known about this as a disaster-related finding.…”
Section: Discussionmentioning
confidence: 88%